The Death Penalty Against Narcotics Traffickers In The Perspective Of Pancasila Justice - satriadi Laupe (Al-Adalah: Jurnal Hukum dan Politik Islam, 2022)
This study discusses the death penalty for narcotics traffickers from the perspective of Pancasila justice. The pros and cons of capital punishment continue to this day, especially narcotics traffickers. The purpose of this study is to determine the imposition of capital punishment on narcotics traffickers in terms of justice according to the views and values in Pancasila. To analyze and understand the death penalty against narcotics traffickers from the perspective of Pancasila justice, this study uses a normative legal research method whose data is obtained through a literature study using analytical descriptive. The results show that basically international law does not require the death penalty, but in Indonesia the death penalty is still allowed, especially for narcotics traffickers and does not conflict with Pancasila and the 1945 Constitution as the results of the judicial review in the Constitutional Court case Number 2/PUUV/2007 stated that the death penalty does not conflict with the Indonesian constitution if it is related to Article 28A and Article 28I paragraph (1) of the 1945 Constitution.